Sistem Perlindungan Konsumen Melalui Pengawasan Kualitas dan Keamanan Produk Pangan - Anak Agung Gde Agung Brama Pramudya; Ni Made Jaya Senastri; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2025)
In the era of globalization and increasing market complexity, consumer protection is a crucial issue, especially regarding food products that have the potential to endanger health. Based on this, how is the legal regulation of consumer protection from food products that have safety risks and how is the legal protection system for food products consumed by the public through BPOM supervision. This research uses normative legal research. The results show that although there are various regulations governing consumer protection, implementation in the field still faces challenges, such as lack of consumer awareness and non-optimal supervision from the authorities. This research emphasizes the need for increased collaboration between the government, business actors and the community to create a more effective supervisory system. Thus, consumers can feel safer and more protected in their transactions, as well as obtain quality food products that are safe for consumption.